Optimalisasi Sumber Daya Alam Lokal melalui Inovasi Keripik Batang Pisang untuk Penguatan UMKM Perempuan di Desa Matang Baloy - Muktar Isnan Hasibuan; Usammah Usammah; Khayranil Ula; Nadia Saputri; Mauliza Mauliza; Uswatun Hasanah; Muhammad Masardi Wardhana; Wilda Ismaira; Nurtasyha Nurtasyha; Muzizah Fitri; Supratman Supratman; Siti Ramna; Dedek Vasliana; Putri Nabila (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2025)
Limited economic diversification in rural communities often results not from the absence of natural resources, but from insufficient community capacity to transform local potential into products with economic value. This community service program aims to optimize the natural resources of Matang Baloy Village through the development of micro, small, and medium enterprises (MSMEs) based on banana stem chip innovation as an effort to empower rural women. The program employed a Participatory Action Research (PAR) approach, actively involving the community—particularly groups of housewives—throughout the stages of problem identification, program planning, action implementation, and activity evaluation. Data were collected through participatory observation, focus group discussions, and continuous mentoring during the training and production processes. The results indicate an improvement in community knowledge and skills in processing banana stems into marketable food products, along with the growing readiness of women’s groups to develop home-based enterprises. Beyond generating product innovation, the program also encouraged positive changes in community attitudes toward the utilization of local natural resources that had previously been underused. The PAR approach played a crucial role in bridging the gap between natural resource potential and community capacity, while strengthening women’s roles as key economic actors at the village level. The conceptual model of PAR–natural resources–MSMEs–women’s empowerment developed in this program demonstrates that innovation based on local potential can serve as a sustainable empowerment instrument when supported by participatory processes.